Stromal Transcription Factor 21 Regulates Development of the Renal Stroma via Interaction with Wnt/β-Catenin Signaling. Issue 7 (28th July 2022) - Finer, Gal; Maezawa, Yoshiro; Ide, Shintaro; Onay, Tuncer; Souma, Tomokazu; Scott, Rizaldy; Liang, Xiaoyan; Zhao, Xiangmin; Gadhvi, Gaurav; Winter, Deborah R.; Quaggin, Susan E.; Hayashida, Tomoko
Key Points: Transcription factor 21 in Foxd1+ interstitial progenitors is required for proliferation and differentiation of the renal stroma. Tcf21 binds to β -catenin and enhances expression of stromal Wnt target genes. The kidney stroma is critical for normal development of the nephron progenitor cells, loop of Henle, and collecting ducts. Visual Abstract: Abstract : Background: Kidney formation requires coordinated interactions between multiple cell types. Input from the interstitial progenitor cells is implicated in multiple aspects of kidney development. We previously reported that transcription factor 21 (Tcf21) is required for ureteric bud branching. Here, we show that Tcf21 in Foxd1+ interstitial progenitors regulates stromal formation and differentiation via interaction with β -catenin. Methods: We utilized the Foxd1Cre;Tcf21 f/f murine kidney for morphologic analysis. We used the murine clonal mesenchymal cell lines MK3/M15 to study Tcf21 interaction with Wnt/ β -catenin. Results: Absence of Tcf21 from Foxd1+ stromal progenitors caused a decrease in stromal cell proliferation, leading to marked reduction of the medullary stromal space. Lack of Tcf21 in the Foxd1+ stromal cells also led to defective differentiation of interstitial cells to smooth-muscle cells, perivascular pericytes, and mesangial cells. Foxd1Cre;Tcf21 f/f kidney showed an abnormal pattern of the renal vascular tree. The stroma of Foxd1Cre;Tcf21 f/f kidney demonstrated marked reduction in β -catenin protein expression compared with wild type. Tcf21 was bound to β -catenin both upon β -catenin stabilization and at basal state as demonstrated by immunoprecipitation in vitro . In MK3/M15 metanephric mesenchymal cells, Tcf21 enhanced TCF/LEF promoter activity upon β -catenin stabilization, whereas DNA-binding deficient mutated Tcf21 did not enhance TCF/LEF promoter activity. Kidney explants of Foxd1Cre;Tcf21 f/f showed low mRNA expression of stromal Wnt target genes. Treatment of the explants with CHIR, a Wnt ligand mimetic, restored Wnt target gene expression. Here, we also corroborated previous evidence that normal development of the kidney stroma is required for normal development of the Six2+ nephron progenitor cells, loop of Henle, and the collecting ducts. Conclusions: These findings suggest that stromal Tcf21 facilitates medullary stroma development by enhancing Wnt/ β -catenin signaling and promotes stromal cell proliferation and differentiation. Stromal Tcf21 is also required for the development of the adjacent nephron epithelia.